Rhythms of Care: Medical Travels beyond the Borders of Bangladesh. Issue 1 (1st March 2020) - McNamara, Karen M.
Abstract: This article examines the experiences of Bangladeshi patients and their families as they travel transnationally within Asia for medical care. I explain how failures of biomedicine in Bangladesh feed into idealized expectations of care abroad. This medical imaginary is fueled by the hope that more expensive treatment in wealthier countries will result in better care, and it is sustained by the way the medical tourism industry operates and the way Bangladeshi patients and their families make choices and engage in the doing of care abroad. A detailed case study of a Bangladeshi cancer patient's prolonged care in Singapore illustrates the tensions and ambivalences in the quest for the best treatment. These tensions are exacerbated by the linguistic, monetary, and emotional challenges faced in traveling back and forth between countries. While patients feel at times betrayed by experiences of care that do not meet their expectations, they also feel compelled to carry on. I capture this dynamic in the term rhythms of care, understanding these as the way the medical imaginary shapes care practices that become a scaffolding for hope to be maintained and further travel to be undertaken. I also reflect on how I become part of these rhythms by acting as the family's interpreter as they navigate health care in Singapore.